The effect of organic and inorganic mulching soil moisture retention : A case study of the trees area in a greenhouse (Mongolian Journal of Geography and Geoecology, 2023)
This study aimed to compare organic and inorganic soil moisture protection mulches and determine how tree growth and soil moisture dynamics change based on experimental research conducted in a greenhouse. We planted three types of trees in sandy soil with consistent regular irrigation and covered them by leaf, straw, stone, sand mulch. We tested organic and inorganic mulches with four groups of 10 replicates. The soil moisture level was measured using a TDR 150 mo del soil moisture meter. The soil moisture sensor was placed at a depth of 12 cm and recorded measurements at intervals of 7-10 days over four months. Compared to the control area, soil moisture was found to be retained by 16.4% more with sand mulch, 19.5% more with stone mulch, 33.9% more with straw mulch, and 40.3% more with leaf mulch. During the measurement period, organic mulch consisting of leaves and straw retained the most moisture and reduced the moisture loss by 20-25%. In terms of plant growth and development, trees with high organic mulch exhibited 20-30% higher growth rates than those in the control area and had trees with diameters 5-10% larger. Our study confirmed that covering the soil has advantages in reducing evaporation from the soil surface, increasing soil moisture, reducing soil compaction, and supporting plant growth and development. Implementing the soil covering to retain moisture enhances the soil property by significantly reducing the need for tree watering and contributing to water conservation. Also, our study indicated that covering materials utilized in this experimental study for soil moisture protection offer numerous advantages, as they are readily available, environmentally friendly, and cost-effective for our country.Хөрсний чийг хамгаалах органик ба органик биш хучаасны нөлөө :   Хүлэмжинд модлог ургамал тариалсан талбайн жишээн дээрХУРААНГУЙ: Хөрсний чийг хамгаалах органик ба органик биш хучаасыг харьцуулан судалж, модны өсөлт, хөрсний чийгийн динамик хэрхэн өөрчлөгдөх, үр дүнг цаашдын судалгааны ажилд ашиглах зорилготойгоор энэхүү судалгааг хийлээ. Судалгаанд TDR 150 загварын SOIL MOISTURE METER хэмжигч багажийг ашиглан хөрсний чийгийг хэмжсэн. Органик ба органик биш хучаасыг дөрвөн хувилбар 10 давталттай, гурван төрлийн модыг элсэнцэр хөрсөнд тариалж ижил хэмжээтэй усалгааг тогтмол хийж туршилтыг явуулсан. Хөрсний чийг хэмжих мэдрэгч 12 см гүнд 7-10 хоногийн давтамжтайгаар (ургамал ургалтын хугацаанд) хэмжилт хийсэн. Хөрсний чийгийг хяналтын хувилбартай харьцуулахад элсэн хучаас 16.4 %, чулуун хучаас 19.5 %, сүрлэн хучаас 33.9 %, навчин хучаас 40.3 %-иар илүү чийгээ хадгалж байна. Нийт хэмжилт хийсэн хугацаанд органик хучаас (навч, сүрэл) хамгийн их чийгийг хадгалж чийг алдагдлыг 20-25 % бууруулж байсан. Тарьцын өсөлтийн  хувьд модны өндрийн үзүүлэлт органик хучаас хяналтын талбайтай харьцуулахад 20-30 %, модны диаметр 5-10 % илүү байна. Хөрсийг хучих нь хөрсний гадаргын ууршилтыг багасгах, хөрсний чийгийг нэмэгдүүлэх, хөрсний нягтралыг бууруулах, ургамлын өсөлтийг дэмжих зэрэг олон давуу талтай байгаа нь энэхүү судалгааны дүнгээр нотлогдож байна. Хөрсний чийг хамгаалах энэхүү туршилт судалгаанд ашиглагдсан хучаасны материалууд нь манай орны хувьд олдоц арвин, байгальд ээлтэй, эдийн засгийн хувьд хэмнэлттэй материал гэдгээрээ давуу тал маш их юм. Бортоготой тарьцны өнгөн хөрсийг   хучиж чийгийг барьснаар хөрсний шинж чанар сайжирч модны усалгааны нормыг багасгаж ус хэмнэх ач холбогдолтой юм.Түлхүүр үгс: Хөрсний чийг, Навчин хучаас, сүрлэн хучаас, чулуун хучаас , элсэн хучаас